Can an Increase in Public Investment Sustainably Lift Economic Growth? - Mourougane, Annabelle (OECD Economics Department Working Papers, 2016)
This paper seeks to identify the conditions under which raising public investment can sustainably lift growth without deteriorating public finances. To do so, it relies on a range of simulations using three different macro-structural models. According to the simulations, OECD governments could finance a ½ percentage point of GDP investment-led stimulus for three to four years on average in OECD countries without raising the debt-to-GDP ratio in the medium term, provided projects are sound. After one year, the average output gains for the large advanced economies of such a stimulus amount to 0.4-0.6%. However, the gains are particularly uncertain for Japan. Reprioritising spending in later years would lead to average long-term output gains of between 0.5 to 2% in the large advanced economies. Those gains depend on the assumptions made on the rate of return. Hysteresis reinforces the case for an investment-led stimulus. Output gains will also be higher if the stimulus is combined with structural reforms and if countries act collectively